Understanding Users' Preferences for Surface Gestures - Morris, Meredith Ringel; Wobbrock, Jacob O.; Wilson, Andy (GI '10 Proceedings of Graphics Interface 2010, 2010)
We compare two gesture sets for interactive surfaces—a set of gestures created by an end-user elicitation method and a set of gestures authored by three HCI researchers. Twenty-two participants who were blind to the gestures’ authorship evaluated 81 gestures presented and performed on a Microsoft Surface. Our findings indicate that participants preferred gestures authored by larger groups of people, such as those created by end-user elicitation methodologies or those proposed by more than one researcher. This preference pattern seems to arise in part because the HCI researchers proposed more physically and conceptually complex gestures than end-users. We discuss our findings in detail, including the implications for surface gesture design.